2020
DOI: 10.1158/0008-5472.can-19-3596
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating Mast Cell–Mediated Stimulation of Estrogen Receptor Activity in Breast Cancer Cells Promotes the Luminal Phenotype

Abstract: Tumor growth and development is determined by both cancer cell-autonomous and microenvironmental mechanisms, including the contribution of infiltrating immune cells. Since the role of mast cells (MC) in this process is poorly characterized and even controversial, we investigated their part in breast cancer (BC).Crossing C57BL/6 MMTV-PyMT mice, which spontaneously develop mammary carcinomas, with MCdeficient C57BL/6-Kit W-sh/W-sh (Wsh) mice, showed that MC promote tumor growth and prevent the development of bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 46 publications
2
35
0
1
Order By: Relevance
“…Intriguingly, a mouse model which involved crossing C57BL/6 MMTV-PyMT mice with mast cell-deficient Wsh mice suggests mast cells may program the developmental circuitry of murine breast cancer cells to a luminal-like subtype by directly enhancing ESR1 transcription. This finding was supported by examination of human breast tumors [26]. Such mast cell-breast cancer cell crosstalk has also been speculated in patients with late-stage, chemotherapy-resistant inflammatory breast cancer as mast cells often resides in close proximity (≤5 µm) to cytokeratin + breast cancer cells [44].…”
Section: The Function Of Mast Cells In Malignant Breast Tumorsmentioning
confidence: 70%
See 2 more Smart Citations
“…Intriguingly, a mouse model which involved crossing C57BL/6 MMTV-PyMT mice with mast cell-deficient Wsh mice suggests mast cells may program the developmental circuitry of murine breast cancer cells to a luminal-like subtype by directly enhancing ESR1 transcription. This finding was supported by examination of human breast tumors [26]. Such mast cell-breast cancer cell crosstalk has also been speculated in patients with late-stage, chemotherapy-resistant inflammatory breast cancer as mast cells often resides in close proximity (≤5 µm) to cytokeratin + breast cancer cells [44].…”
Section: The Function Of Mast Cells In Malignant Breast Tumorsmentioning
confidence: 70%
“…A recent trend in the field has been to breed mast cell-deficient mice with strains engineered to develop spontaneous or oncogene-inducible tumors. This has fueled new discoveries that help map the role of mast cells in skin- and breast-derived cancers [ 20 , 26 ]. For example, in an HPV-induced squamous cell carcinoma (SCC) murine model with Mcpt5-Cre + R-DTA + mast cell-deficiency, mast cell status did not alter tumor growth or angiogenesis, contradicting an earlier study that used a c-Kit-dependent mast cell-deficiency model [ 19 , 20 ].…”
Section: The Mast Cell—tumor Controversymentioning
confidence: 99%
See 1 more Smart Citation
“…The protumoral and antitumoral role of mast cells in BC progression is still controversial 31 . Studies showed that mast cells increased BC growth and metastasis 32 , but the study by della Rovere et al revealed that peritumoral mast cells seemed to have a cytolytic activity against tumor cells 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an in vitro animal experiment showed that coinjection of mast cells and HER2-positive breast cancer cells increased tumor engraftment and outgrowth in mice. [33] Additionally, a high level of mast cells in extratumoral benign prostate tissues was considered a risk factor for a poor prognosis in prostate cancer patients. [34] Mechanistically, it was observed that tumor-derived microvesicles from non-small-cell lung cancer (NSCLC) cells are internalized by mast cells, which enhances the migratory ability of mast cells and promotes the release of TNF-alpha and MCP-1.…”
Section: Discussionmentioning
confidence: 99%